Role of slow breathing exercise on lung function status in depressive illness patients - Afreen, Khandaker Nadia; Rahman, NM Wahidur; Ainan, Sayema; Ferdous, Mehboba; Fahmi, Sonia; Akter, Mahbuba (Mediscope, 2016)
Major depressive disorder (MDD) is associated with depressed lung function. This depressed lung function can be improved by slow breathing exercise ((SBE). To observe peak expiratory flow rate (PEFR) in newly diagnosed MDD patients and after three months of regular practice of SBE. This prospective study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from January to December, 2014 to assess the lung function status in MDD patients. For this, 30 newly diagnosed MDD patients, aged 20 to 50 years were enrolled from the Department of Psychiatry of BSMMU. PEFR of all subjects were assessed by a portable digital spirometer before and after three months of regular practice of SBE. There was significant improvement of lung function status found when compared PEFR between before and after three months of regular practicing of SBE. From this study it may be concluded that SBE is very effective and potent method for improvement of poor lung function associated with all types of pulmonary functional disorder in MDD. Mediscope Vol. 3, No. 2: July 2016, Pages 26-30